Digital signal processing implementations : - Singh, Avtar (Thomson, 2004)
Bridging the gap between Digital Signal Processing theory and design, this implementation-oriented textbook is based on the authors' extensive experience in teaching graduate and undergraduate courses on the subject. The objective of the book is to help students understand the architecture, programming, and interfacing of commercially available programmable DSP devices, and to effectively use them in system implementations. Throughout the book, the authors utilize a popular family of DSP devices, viz., TMS320C54xx from Texas Instruments. In the end, students will be comfortable in using both hardware and software for designing with the programmable DSP devices.